### Home > CAAC > Chapter 4 > Lesson 4.1.1 > Problem 4-5

4-5.

Use the eTool to manipulate the Algebra tiles to help you with this problem.

Click the link at right for the full version of the eTool: AC 4-5 HW eTool

Be sure to know how to get this equation.

1 + (−3) − (−2*x*) = (−*x*) + (−3) − 2 − (*x*)

Change all subtraction to addition and combine like terms.

Add 2 to both sides.

Move the variable to one side of the equation.

1 + (−3) + 2*x* = (−*x*) + (−3) + (−2) + (−*x*)

−2 + 2*x* = −2*x* + (−5)

−2 + 2*x* = −2*x* + (−5)

+2 +2

2*x* = −2*x* + (−3)

2*x* = −2*x* + (−3)

+2*x* +2*x*

4*x* = −3

*x* = −0.75

Insert the number you got for *x* into your original equation to make sure it is correct.